Husserl on Lifeworld and Experiential World - Yu, Chung-Chi (SocietàMutamentoPolitica, 2016)
Husserl brings up the lifeworld notion in his discourse on overcoming the crisis of European sciences that results from the objectivism or naturalism of scientific research. He puts forward the concept of experiential world as he works on the foundation for socio-cultural sciences. Both concepts depict how the subject is not enclosed in itself, it is instead the subject in the world. Yet the distinction of lifeworld and experiential world reveals that Husserl thematizes this problem in two distinguished ways, the one has the transcendental phenomenology as background, the other the phenomenological psychology. My paper aims at an explication of these two different ways of how Husserl deals with the relationship between subject and the world and explores the possibility of an lifeworld discourse that looses itself from the transcendental bond.